Optimizing English Vocabulary Acquisition in Fashion Design Students through Project-Based Learning Strategies at the Vocational Level - Radita, Cindy; Yuniar, Rendhi Fatrisna (Proceeding of International Conference on Islamic Education (ICIED); Vol 9 No 1 (2024): Proceeding of International Conference on Islamic Education (ICIED)DO - 10.18860/icied.v9i1.3149, 2024)
This classroom action research aims to enhance English vocabulary acquisition among 27 eleventh-grade students enrolled in the Fashion Design program at SMK Negeri 7 Malang, Indonesia. The study employs Project-Based Learning (PBL) to address vocabulary learning challenges specific to the fashion design context. The research follows the stages of planning, action, observation, and reflection to evaluate the effectiveness of PBL in improving vocabulary skills. Data collection methods included vocabulary assessments, student surveys, and teacher observations, providing a comprehensive understanding of the intervention's impact. The results reveal a significant improvement in students' vocabulary mastery, particularly in fashion design major, after implementing PBL. The approach fostered active student engagement through real-world projects, leading to increased motivation and a deeper understanding of relevant vocabulary. Surveys indicated heightened enthusiasm for learning English, with students expressing greater confidence in using specialized terms. This research demonstrates the potential of integrating PBL into the curriculum to support vocabulary development in vocational education, suggesting that such strategies could be beneficial across various fields.